2011
DOI: 10.1088/1748-9326/6/3/034026
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hygroscopicity and morphology during ageing of diesel soot

Abstract: Soot particles are an important component of atmospheric aerosol and their interaction with water is important for their climate effects. The hygroscopicity of fresh and photochemically aged soot and secondary organic aerosol (SOA) from diesel passenger car emissions was studied under atmospherically relevant conditions in a smog chamber at sub-and supersaturation of water vapor. Fresh soot particles show no significant hygroscopic growth nor cloud condensation nucleus (CCN) activity. Ageing by condensation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
172
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(202 citation statements)
references
References 44 publications
24
172
0
Order By: Relevance
“…10. As discussed in detail by Tritscher et al (2011b), the measured growth factor depended on the particle size selected for the measurement. We show here only the case of 200 nm particles to represent the size range investigated here.…”
Section: Water Uptake In Soot Particlesmentioning
confidence: 95%
See 1 more Smart Citation
“…10. As discussed in detail by Tritscher et al (2011b), the measured growth factor depended on the particle size selected for the measurement. We show here only the case of 200 nm particles to represent the size range investigated here.…”
Section: Water Uptake In Soot Particlesmentioning
confidence: 95%
“…It was found that the formed SOA mass is significant: after five hours of aging about 80 % of the total organic aerosol was on average secondary. These measurements were complemented by Tritscher et al (2011b) who investigated the water uptake at sub-saturation and cloud condensation nuclei (CCN) activity of the fresh and photochemically aged soot from the same diesel passenger cars. Fresh diesel soot particles were found to be non-hygroscopic, i.e.…”
mentioning
confidence: 99%
“…The particles after the structural change (collapse) become less fractal or more compact, which results in decreased electrical mobility diameter, and thus leads to shrinkage (hygroscopic GF<1) or underestimated hygroscopicity obtained by diameter-based methods. The restructuring has been observed for different soot types (Weingartner et al, 1995;Tritscher et al, 2011) and for particles with a Dd >100 nm (Martin et al, 2012). The hygroscopic GF for the LH 15 mode increased monotonically and in a modest way (from 1.31 to 1.38) with particle size, while the fraction of particles in the LH mode increased with diameter from 29% to 59%.…”
mentioning
confidence: 81%
“…Particles with median dry diameters of 20,50,75,110 and 145 nm were preselected in a narrow quasi-monodisperse size range by a 10.9-cm long Vienna-type differential mobility analyser (DMA1). The dry diameters were selected considering the shape 20 of the particle number size distribution in Budapest to cover the Aitken and accumulation modes.…”
mentioning
confidence: 99%
“…At sites like CES, which are classified as background sites but located relatively close to 25 urban agglomerations (20 and 30 km from Rotterdam and Utrecht, respectively), the observed organic matter might have been processed sufficiently to become more hygroscopic than what is normally observed in the urban environment (e.g., Ervens et al, 2010). For black carbon (BC) we use κ = 0 (e.g., Hitzenberger et al, 2003;Rose et al, 2011;Tritscher et al, 2011).…”
Section: Hygroscopicity Parameter Kappa (κ) and Ccn Closurementioning
confidence: 99%